Development of Copper-Aluminum Layered Double Hydroxide in Thin Film Nanocomposite Nanofiltration Membrane for Water Purification Process - Tajuddin, Muhammad Hanis; Yusof, Norhaniza; Wan Azelee, Ihsan; Wan Salleh, Wan Norharyati; Ismail, Ahmad Fauzi; Jaafar, Juhana; Aziz, Farhana; Nagai, Kazukiyo; Razali, Nor Faizah (Frontiers in Chemistry, 2019)
This study aims to fabricate a thin film composite (TFC) membrane, modified with copper-aluminium layered double hydroxide (LDH) nanofillers via interfacial polymerization technique for nanofiltration (NF) processes. It was found that Cu-Al LDH nanofillers possessed layered structured materials with typical hexagonal plate-like shape and positive surface charge. The study revealed that TFN membrane exhibits a relatively smooth surface and a less nodular structure compared to pristine TFC membrane. The contact angle of TFN progressively decreased from 54.1˚ to 37.25˚, indicating enhancement in surface hydrophilicity. Moreover, the incorporation of LDH nanofillers resulted in a less negative membrane as compared to the pristine TFC membrane. The best NF performance was achieved by TFN2 membrane with 0.1% of Cu-Al LDH loading and a water flux of 54.62 Lm-2h-1 at 7 bar. The addition of Cu-Al LDH resulted in excellent single salt rejections of Na2SO4 (96.8%), MgCl2 (95.6%), MgSO4 (95.4%), and NaCl (60.8%). The highest rejection of Na2SO4 (96.8%), MgSO4 (95.4%), MgCl2 (95.6%) and NaCl (63.7%) were also achieved by the TFN embedded with 0.1% Cu-Al LDH loading in polyamide layer.The improvement in anti-fouling properties of resultant TFN membranes can be observed from the increments of pure water flux recovery and normalized water flux by 14% and 25% respectively. The findings indicated that Cu-Al LDH is a promising material in tailoring membrane surface properties and fouling resistance. The modification of the LDH-filled TFN membrane shows another alternative to fabricating a high-performance composite membrane, especially for water softening and partial desalination process.